A review on internet of things (IoT) based water monitoring system - Malaika Shaikha; Azad Alia; Riaz Ahmed; Babar Ali Shaikh (Penerbit Universiti Kebangsaan Malaysia, 2023)
Current advancements in sensor networks are crucial for environmental remediation. The Internet of Things (IoT) connects numerous devices that may share and collect data. IoT expands its capabilities to include environmental concerns in addition to the automation sector by utilizing industry 4.0. Polluted water has emerged as one of the most serious dangers in latest days since drinking water has been contaminated and polluted. Contaminated water may trigger a variety of illnesses in humans and animals, affecting the ecosystem’s life cycle. This means, there is an increased demand for water which might affect the available sources of water at large. Therefore, effective management and monitoring of available resources of water is the need of the hour. This review paper includes the use of Internet of Things (IoT) technology for physical parameters of the water monitoring systems to manage and save scarce water resources. The traditional method to monitor water quality and quantity has been a quite difficult task involving a large amount of labour and cash. But the IoT application slashes human involvement and most of the procedural decisions are made by algorithms. Thus, smart methods for investigating water contamination are becoming increasingly significant with advancements in sensors, communication, and IoT technologies. A water monitoring system (WMS) is a low-cost and feasible system that uses IoT technology to analyse the quality of drinking water. use of IoT tools for water monitoring will be a step in the right direction. Even though there are many great technological advancements for the surveillance of water quality, the research field is still challenging. This article aims to unveil the recent research for developing intelligent, energy-efficient, and highly effective water monitoring systems that will allow for continuous monitoring of water in less privileged areas of Pakistan. This article will assist researchers and administrative organizations in starting pertinent investigations of water in rural areas by utilizing a WMS.